Perancangan Dan Implementasi Sistem Informasi Pengelolaandata Inventaris, Aset, Dan Keuangan Berbasis Web (Studi Kasus Desa Sawo Jajar Kecamatan Kotabumi Utara) - Kurnia Sari, Bella; Yulina, Yulina (Universitas Pakuan, 2025)
DESIGN AND IMPLEMENTATION OF WEB-BASED INVENTORY, ASSET, AND FINANCIAL DATA MANAGEMENT INFORMATION SYSTEM (CASE STUDY OF SAWO JAJAR VILLAGE, NORTH KOTABUMI DISTRICT)The management of inventory, assets, and financial data in Sawo Jajar Village is still carried out manually using notebooks and separate files, which often leads to difficulties in searching for data, a high risk of document loss, and inaccurate information in the reporting process. These limitations reduce transparency and administrative efficiency in the village. This study aims to design and develop a Web-based information system that can assist village officials in managing inventory, assets, and finances in an integrated, effective, and easily accessible manner. This research employs the Waterfall development method, which consists of requirement analysis, system design, implementation, testing, and maintenance stages. The system was developed using PHP as the programming language, MySQL as the database, and Bootstrapp as the user interface framework. The main features of the system include inventory data management, asset management, recording of financial income and expenditures, automatic report generation, and report printing. The results of system implementation show that the system accelerates the recording and reporting processes, improves data accuracy, and enables real-time monitoring of village assets and finances. Based on testing using the black box method, all system functions run according to user needs. Therefore, this Web-based information system is proven to improve transparency and efficiency in the administrative processes of Sawo Jajar Village.